2017
DOI: 10.1155/2017/6841239
|View full text |Cite
|
Sign up to set email alerts
|

On the Potential of 25 Years (1991–2015) of Rawinsonde Measurements for Elucidating Climatological and Spatiotemporal Patterns of Afternoon Boundary Layer Depths over the Contiguous US

Abstract: The daytime planetary boundary layer (PBL) depth is an essential parameter in, for example, dispersion models and numerical weather prediction. We applied a recently developed technique to estimate afternoon PBL depths from 516,887 daily rawinsonde measurements obtained at 0000 UTC between 1 Jan 1991 and 31 Dec 2015 from 67 US sites. We discuss salient features in the PBL depth variability and examine the climatology of afternoon PBL depths as a function of geographical region and Köppen-Geiger climate regime.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
(76 reference statements)
1
19
0
Order By: Relevance
“…For instance, the mean summertime precipitation over 1981–2010 was 5.9 cm, and year‐to‐year variability was extreme with a drift of summer precipitation of around −5‐4 cm. Deep ABL in summer over such climatic regions in the United States are not unusual, as reported in previous studies (Lee & Pal, ; Seidel et al, ). Both rawinsonde sites at San Diego and Oakland are characterized by urban hotspots which likely trigger high summer time BLDs under offshore flow.…”
Section: Resultssupporting
confidence: 82%
“…For instance, the mean summertime precipitation over 1981–2010 was 5.9 cm, and year‐to‐year variability was extreme with a drift of summer precipitation of around −5‐4 cm. Deep ABL in summer over such climatic regions in the United States are not unusual, as reported in previous studies (Lee & Pal, ; Seidel et al, ). Both rawinsonde sites at San Diego and Oakland are characterized by urban hotspots which likely trigger high summer time BLDs under offshore flow.…”
Section: Resultssupporting
confidence: 82%
“…We estimated the daily afternoon BLDs from the 00 UTC soundings over the 10 sites (Figure 1a) using a recently developed method based on the analyses of bulk Richardson number ( Ri b ) (Koffi et al, 2016; Lee & De Wekker, 2016; Lee & Pal, 2017). From the profile of Ri b , we estimated the ABL top as the height at which the Ri b first exceeded 0.25 (e.g., Vogelezang & Holtslag, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, a number of studies (Carlson & Ludlam, ; Lanicci & Warner, ) found the elevated terrains of Mexico to be one of the major sources of EMLs; these potentially warm EMLs also were found to have a northward expansion into the Rocky Mountains. Figure b suggests relatively deeper ziFD (>2,500 m AGL) over the R5 sites (Midland, Santa Teresa, and Del Rio) compared to the other sites in the Southern Great Plains, which could be attributed to the ABL features over dry warm arid regions like the southwest United States (Lee & Pal, ).…”
Section: Resultsmentioning
confidence: 96%
“…Using an improved version of the bulk Richardson number (R ib ) approach (Lee & De Wekker, 2016;Lee & Pal, 2017), we computed the daily afternoon BLDs from the 00 UTC soundings available from the Integrated Global Radiosonde Archive (IGRA; Durre et al, 2006) for 22 sites (Figure 1). We determined the top of the ABL as the height at which the R ib first exceeded 0.25 (e.g., Seidel et al, 2010Seidel et al, , 2012Vogelezang & Holtslag, 1996).…”
Section: Data Sets and Methodsmentioning
confidence: 99%
See 1 more Smart Citation